Cigarette smoking status alters dysbiotic gut microbes in hypertensive patients - Pan Wang; Ying Dong; Jie Jiao; Kun Zuo; Chunming Han; Lei Zhao; Shu Ding; Xinchun Yang; Mulei Chen; Jing Li (The Journal of Clinical Hypertension, 2021)
Abstract Smoking not only is one of the most important risk factors of hypertension (HTN), but also alters the composition of gut microbiota (GM) in previous studies. Although dysbiosis of GM has been implicated in HTN, how GM alters in patients with HTN under smoking status is still not clear. This study aimed to explore the difference in intestinal microflora among smokers with HTN (S‐HTN), nonsmokers with HTN (NS‐HTN), and smokers without HTN (S‐CTR) and identify whether cigarette smoking led to disordered intestinal microbiota in patients with HTN. Metagenomic sequencing analysis of fecal specimens was conducted in nonsmokers without HTN (NS‐CTR, n = 9), S‐CTR (n = 9), NS‐HTN (n = 18), and S‐HTN (n = 23). Compared with S‐CTR or NS‐HTN, the GM in S‐HTN was disordered, with lower microbial α‐diversity and significant difference of β‐diversity on axes as compared to S‐CTR at genus and species level. The microbial enterotype in S‐HTN was inclined to Prevotella‐dominant type. Dramatic changes in the intestinal genera and species composition were observed in S‐HTN, including reduced enrichment of Phycisphaera and Clostridium asparagiforme. Moreover, the intestinal function altered in S‐HTN. Therefore, the findings of the present study revealed GM disorders in S‐HTN and clarified the role of smoking in impairing the intestinal microbiome in HTN. Tobacco control is particularly important for improving GM in patients with HTN, and might be beneficial in preventing future cardiovascular events.